Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1990
DOI: 10.1182/blood.v76.1.178.178
|View full text |Cite
|
Sign up to set email alerts
|

Regulation and lectin activity of the human neutrophil peripheral lymph node homing receptor

Abstract: We characterize the nature and regulation of a human neutrophil cell surface antigen recognized by monoclonal antibodies (the DREG series) against a human lymphocyte peripheral lymph node homing receptor. Human neutrophils express high levels of the DREG antigen, whose expression is downregulated after treatment with phorbol myristate acetate, or the chemotactic factors C5a and FMLP. Interestingly, C5a treatment also downregulated the monocyte DREG antigen, but had no effect on expression of the lymphocyte mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1992
1992
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…The activation of leukocytes by phorbol esters, chemoattractants, or various cytokines induces rapid (in minutes) endoproteolytic processing (shedding) of L-selectin from the cell surface [10][11][12]. We and others have shown that blocking L-selectin shedding dramatically reduces leukocyte rolling velocities and enhances leukocyte accumulation on endothelial ligands of L-selectin in vitro [13] and in vivo [14], which indicates that L-selectin shedding contributes in regulating L-selectin adhesion.…”
Section: Introductionmentioning
confidence: 82%
“…The activation of leukocytes by phorbol esters, chemoattractants, or various cytokines induces rapid (in minutes) endoproteolytic processing (shedding) of L-selectin from the cell surface [10][11][12]. We and others have shown that blocking L-selectin shedding dramatically reduces leukocyte rolling velocities and enhances leukocyte accumulation on endothelial ligands of L-selectin in vitro [13] and in vivo [14], which indicates that L-selectin shedding contributes in regulating L-selectin adhesion.…”
Section: Introductionmentioning
confidence: 82%
“…Effects of cytokines and mitogens on endothelial cell ligands of leukocyte adhesion molecules have been studied in detail. IL1, TNF and LPS increase the expression of ICAM-1,ELAM-1 and VCAM-1 on human umbilical vein endothelial cells, and to promote the adherence of leukocytes to these activated endothelial cells [5].Therefore, it is interesting to find out that the same inducers also affect the homing receptor status of lymphocytes, peripheral blood leukocytes and bone marrow cells ( [16][17][18][31][32][33][34] and the present report). Thus, cytokines and mitogens can delicately control the extravasation of leukocytes at several steps.…”
Section: Molecular Form Of L-selectin On Cultured Cellsmentioning
confidence: 99%
“…the cell upon activation with PMA or physiological activating factors, such as chemoattractants [6,27,28,39, 401.…”
Section: Characterization Of Bovine Leukocyte Lecam-1mentioning
confidence: 99%